472 Accuracy of Documentation and Handover of Surgical Operation Details in Cardiac Surgery. (19th August 2022) - Hara, N; Volpi, S; Yates, M; Corredor, C; Shipolini, A
Abstract: Introduction: GMC Good Medical Practice Guideline states that documentation must be clear, accurate and legible. Accurate documentation of operation notes ensures proper postoperative care and forms important legal documents. This audit aims to assess the accurateness and consistency of recorded operation names throughout patients' hospital stay following cardiac surgery, as well as the effect of standardisation of operation names to improve the accuracy of documentation. Method: Patients undergoing cardiac surgery at St. Bartholomew's Hospital from November 29 to December 10, 2021, had data prospectively collected from their electronic patient records, which were compared to the standardised operation name. After the first audit cycle, junior medical staff were educated on the standardisation of operation names. Electronic patient records were reviewed again for patients undergoing cardiac surgery from January 10 to January 20, 2022. Results: Following intervention, there were significant improvements in the accuracy of documented operation details. Initially, 65% of operation notes were accurately documented, whereas 96% of operation notes were completed to the ideal standard post-intervention. There was a 37% increase in the number of accurate discharge summaries, while inaccuracies and missing operation names were reduced to 0% from the initial 12%. Conclusions: Accurate documentation of operation details is expected by GMC standards. Poor documentation can hinder the quality-of-care patients receive postoperatively. We have shown variation in descriptions of standard operations and multiple inaccuracies throughout patients' hospital stay. We suggest agreed standardisation of operation details and education of junior medical staff regarding accuracy of documentation to enhance compliance with the GMC standard.